Pathways for the sustainable intensification of wheat production under current and future climate change scenarios in the Mediterranean region - Tita, Davide (2024)
This scientific inquiry delves into the far-reaching implications of global warming and the continuous emission of anthropogenic greenhouse gases into the Earth's atmosphere. With a primary focus on the semi-arid regions of Morocco, the study broadens its perspective to conduct a comparative analysis of similar challenges faced by Spain, Egypt, Italy, Jordan, Turkey, and Iran. The paper aims to illuminate the intricate interplay between climate change and agriculture, underscoring the imperative for sustainable practices to alleviate the detrimental impacts on food security and economic stability. The methodology employed centers around the utilization of the DSSAT (Decision Support System for Agrotechnology Transfer) model, a reliable tool for simulating yield across different seasons. This study evaluated the performance of wheat varieties in MENA (Middle East and North Africa) regions and some in the Mediterranean area. Optimal yields were observed under treatments involving sprinkler or furrow irrigation of 60-140 mm and nitrogen application ranging from 60 to 120 kg/ha, resulting in an average yield trend of around 6 t/ha. The identified optimal seeding date was the 1st of November, with conservation or adaptation practices demonstrating superior outcomes. This finding was further validated by climate change projections, estimating yields of up to 6.4 t/ha in Spain and a slight increase in Morocco and in one of the sites in Jordan, alas a reduction of 20% in Italy and up to 88% in Iran at the end of the century. The study's significance lies in its evaluation of nutrient and water trends in the MENA and Mediterranean regions. It offers farmers and policymakers valuable insights to guide a sustainable transition, both economically and ecologically.